Concurrently wireless sensor network using microcontroller for home monitoring against fire - Putu Wiweka Prasetyananda; Sunny Arief Sudiro; Bheta Agus Wardijono (JURNAL INFOTEL, 2022)
This paper proposes a prototype fire monitoring system with Wireless Sensor Network (WSN) in order to detect fires in several places at once and facilitate the placement of the detection. WSN is a technology where several sensors work together to establish communication over a wireless network. This prototype fire monitoring system can be monitored through the website in real time and the detection data is stored on the cloud server. This prototype fire monitoring system uses 4 sensor nodes, each of which is placed in several places to detect fires and sends the detection results to the master node. The master node receives and processes the data sent by the sensor node to generate 16 different conditions concurrently, in the event of a fire it will send a telegram message and the condition data to the cloud server. Several attempts to send data from the sensor node to the master node were completely successful and sending data from the master node to the cloud server as well as sending notification messages have been sent properly.